Mating disruption technology: An innovative tool for managing yellow stem borer (Scirpophaga incertulas Walker) of rice in Indonesia: Teknologi gangguan kawin: Inovasi untuk pengendalian penggerek batang kuning (Scirpophaga incertulas Walker) pada padi di Indonesia - Iqbal, Muhamad; Marman, Maulana; Arintya, Fridia; Broms, Kristin; Clark, Thomas; Srigiriraju, Lakshmipathi (Jurnal Entomologi Indonesia, 2023)
Yellow stem borer (YSB) of rice, Scirpophaga incertulas Walker, causes significant damage to rice production in Indonesia. YSB management largely depends on insecticide applications and alternative management practices are very few and impractical. Pheromone-mediated mating disruption (MD) is a new way to manage YSB while reducing dependence on conventional insecticides. Pheronâ„¢ RSB is an low-density polyethylene (LDPE) MD dispenser, containing 1.25 g of a four-way blended insect sex pheromone components - Z11-Hexadecenal, Z9-Hexadecenal, Z13-Octadecenal, Z9-Octadecenal in a ratio of 75, 8.6, 9.4, and 7 respectively. The objective is to evaluate MD by Pheronâ„¢ RSB as a tool for season-long management of YSB. Dispensers were applied at a rate of 20 dispensers/ha in a minimum area of 4 ha. We conducted these trials at 74 locations, non-replicated, across Java, in the wet and dry seasons of 2020–2021 where YSB are endemic and problematic. Efficacy of MD in pheromone foundational practice (PFP) was compared to conventional grower practice (CGP). Trap reduction, a measure of MD was significantly higher (>70%) in PFP as compared to CGP. A major benefit of MD is reduction in damage. Significantly lower damage to rice tillers (40–46%) was seen in PFP compared to CGP. Lower damage in PFP likely protected yield by 0.43 to 0.76 ton/ha compared to CGP. Compared to PFP, CGP required 40–56% higher insecticide applications to manage YSB.  Pheronâ„¢ RSB provided season-long MD and proved to be a powerful tool for integrated management of YSB.